The Effect Of Price, Transaction Security, Online Consumer Review, and Viral Marketing on Purchase Decision in E-Commerce Shopee - Aulia Safira Sholichin; Wisnalmawati Wisnalmawati (Universitas Tidar, 2021)
This study aims to determine the effect of price, transaction security, online consumer reviews, and viral marketing on purchase decisions in e-commerce shopee (a survey of students domiciled in Sleman). The sampling technique used in this study is accidental sampling, provided that 100 respondents have made a purchase in the e-commerce Shopee. The analysis technique used is multiple linear regression analysis. From the results of this study it is known that price, transaction security, online consumer reviews, and viral marketing together (simultaneously) have an effect on purchase decisions in e-commerce Shopee among students domiciled in Sleman at a significance level of 0.00 <0.05 and The Adj R square value is 65.9%, meaning that the variable price, transaction security, online consumer review, and viral marketing is able to explain 65.9% of the purchase decision variable and the remaining 34.1% or 0.341 is influenced by variables outside of this study. Then partially, the four variables consisting of price, transaction security, online consumer review.